Genomic trajectories of colorectal cancer with choroidal metastasis: longitudinal insights from tissue and liquid biopsy via next-generation sequencing - Ottaiano, Alessandro; Circelli, Luisa; Picone, Carmine; Ianniello, Monica; Ruggiero, Raffaella; Sirica, Roberto; Santorsola, Mariachiara; Carratù, Anna Chiara; Petrillo, Nadia; Cerbone, Gaetana; Sabbatino, Francesco; Berretta, Massimiliano; et al. (Frontiers in Genetics, 2025)
Colorectal cancer (CRC) is a leading cause of cancer-related death, with metastases typically involving the liver, lungs, and peritoneum. Choroidal metastases are extremely rare. We report a case of metastatic CRC with choroidal involvement, characterized by longitudinal genomic profiling using the TruSight Oncology 500® assay. A 66-year-old man with rectosigmoid junction CRC initially showed RAS/BRAF wild-type status, microsatellite stability (MSS), and a moderate tumor mutational burden (TMB: 7.1 mutations/Mb) on the primary tumor. First-line chemotherapy combined with anti-EGFR therapy was initiated for synchronous liver metastases. Upon the development of visual symptoms, imaging confirmed choroidal metastasis. Circulating tumor DNA (ctDNA) analysis revealed persistence of the TP53 p.E286K mutation and marked clonal evolution. Newly emerged Tier IA alterations included EGFR amplification and JAK2 p.V617F mutation, alongside multiple Tier IIC and IID variants absent in the primary tumor. The ctDNA also revealed a hypermutated phenotype (TMB: 44.9 mutations/Mb). To our knowledge, this is the first report integrating both tissue- and liquid-based NGS in a CRC case with ocular metastasis. These findings highlight the value of comprehensive genomic monitoring in metastatic CRC and may offer insights into the molecular landscape of rare metastatic sites such as the choroid.